Entextualizing affective meanings: Translingual practices in Cape Verdean music video reception. (April 2023) - Hansen, Kimberly S.; Sun Han Chang, Lyana L.; Suresh Canagarajah, A.
Abstract: Multilingual interactions on digital platforms such as YouTube reveal complex translingual practices and negotiation strategies on the part of viewers. Two live performances sung in Cape Verdean Creole (Kriolu) by Mayra Andrade, a Cape Verdean music artist, uploaded to YouTube by different digital media platforms generated these types of interactions. These interactions were analyzed by adopting Wortham and Reyes' (2015) "discourse analysis beyond the speech event" to reveal the extent to which semiotic resources utilized in the performances, and translingual practices and negotiation strategies utilized by the viewers, brought about uptake of the Cape Verdean Creole lyrics and their meaning, and artist identity. The data revealed that viewers negotiated language related themes and artist and viewer identity in different ways, yet shared similar appreciation for the performances and the artist. Additional concepts, such as phatic communication and nonrepresentational meaning, provide further understanding for viewers' attitudes towards negotiating meaning and engaging in a digital forum to discuss with others their reactions to and love of the artist's live performances. The study reveals the diverse semiotic resources adopted by nonlocal audiences to appreciate nonrepresentational meanings to redress the current emphasis on representational meanings and linguistic resources in translingual studies.